Tożsamość w płynie: "homo aestheticus" między regałami - Sułkowska-Janowska, Mariola (Folia Philosophica, 2018)
The paper deals with the problem which seems to be one of dominant features of postmodern discourse, that is, the problem of identity. The author supplements the philosophical and sociological attitude towards this issue with aesthetical context, which, as it shows up, defines some important elements that co-determine the process of postmodern auto-creation. The trans-categorial notion of “aesthetic identity”, emerging from this process, which exceeds and at the same time gathers different aspects of “identity” discourse, emphasises first of all the bodily aspect and its surprising, especially from the point of view of traditional philosophy, role in creating liquid, performative postmodern identity.